Serum LH level prior to progestin administration is significant on pregnancy and live birth in programmed frozen-thawed embryo transfer cycles - Guler, Ismail; Demirdag, Erhan; Akdulum, Munire F. C.; Polat, Mert; Erdem, Ahmet; Erdem, Mehmet (Frontiers in Endocrinology, 2023)
Purpose To evaluate the impact of serum LH levels prior to progestin administration on the outcomes of programmed frozen-thawed embryo transfer (FET) cycles. Methods Retrospective cohort study was conducted to compare the treatment outcomes between four groups based on the 25 percentiles of serum LH levels before progestin administration in 596 cycles of 518 patients undergoing artificial endometrial preparation protocols for FET. Primary outcome measures were ongoing and live birth rates. Secondary outcome measures were the pregnancy rates, clinical pregnancy rates, and pregnancy loss rates. Results The trends in clinical pregnancy (CPR) and live birth rates (LBR) increased from the first to the fourth quartile (Q1 to Q4) of serum LH levels prior to progestin administration (37,0% to 48,3%, p = 0.042, and 22.6% to 39.5%, respectively, p = 0.003). Pregnancy loss rates (PLR) were higher in group Q1, although the difference was not statistically significant. Based on a multivariate logistic regression analysis, a low serum LH level before progestin initiation was found to be the most significant predictor associated with a negative effect on live birth (OR: 0,421, 95% CI 0,178 – 0,994, p=0,048). The day of estrogen initiation was significantly correlated with serum LH levels and quartiles of serum LH levels before progestin administration (r=0,200, p=0,015 and r=0,215, p=0,009, respectively). Conclusion The serum LH level prior to progestin administration significantly affects pregnancy and live birth rates in patients undergoing an artificial endometrial preparation protocol for FET. LH monitoring should be incorporated into the follow-up, in addition to assessing endometrial thickness and morphology in artificial FET cycles.